THE ANALYSIS OF METHODOLOGIC CHARACTERISTICS OF RESEARCHES ON SOCIAL AND ECONOMIC BURDEN OF DISEASES IN RUSSIA IN THE FRAMES OF DEVELOPMENT OF STANDARD COST OF ILLNESS METHODOLOGY FOR THE HEALTH TECHNOLOGY ASSESSMENT - V. I. Ignatyeva; M. V. Avxentyeva (Фармакоэкономика)
the concept of the relations between public health and national economy has appeared long time ago, but the development of quantitative methods started only in the middle of the XXth century. Until now there are no uninamioulsly accepted methods and approaches for this type of research. The cost of illness method (assessment of social and economic burden of disease) is one of the most widely used. Our objective was to analyze the methodologic characteristics of researches on the cost of illness in Russia for the development of the standard methodology on evaluation of the social and economic burden related to cancers to be used further for the health technology assessment. Materials and methods. Based on the results of studying foreign and national guidelines and publications devoted to the methodological issues of the cost of illness methods, we worked out the criteria list for analysis of the methodological characteristics of this type of research. Further the developed criteria list was used to study the publications on the results of cost of illness studies in Russia. Results. In total we have analyzed 6 publications on cost of illness related to cancers and 10 publications on assessement of burden related to other diseases. The analysis was considerably hampered by the insufficient description of used methods in the majority of publications. Nethertheless we have discovered major discrepancies in the choice of methods and approaches to the assessment of the disease burden, which makes impossible comparison or use of their results for the health technology assessment. Conclusions. The undertaken analysis highlightened the need for development of standardised methods as well as standardised reporting, which would allow use of research results for health technology assessment and decision making on the financing and health care management.